Clinical effect of kyphoplasty in the treatment of osteoporotic thoracolumbar compression fractures in patients with diabetes - Gao, Xiangcheng; Du, Jinpeng; Huang, Yunfei; Li, Shuai; Hao, Dingjun; He, Baorong; Yan, Liang (Frontiers in Surgery, 2023)
Objective To study the clinical effect and influencing factors of kyphoplasty in the treatment of osteoporotic thoracolumbar compression fractures (OTCF) complicated with type 2 diabetes mellitus (T2DM). Methods A total of 472 patients with OTCF complicated with diabetes who were enrolled in our hospital from January to December 2019 were selected as the study subjects, and all patients were treated with percutaneous kyphoplasty (PKP). The effects of gender, age, smoking, drinking, body mass index (BMI), bone mass density (T score), fasting blood glucose level, fasting C-peptide, glycosylated hemoglobin, course of T2DM, vertebral segment and surgical instrument on postoperative improvement were analyzed. The quality of life was evaluated by visual analog score (VAS) and Oswestry disability index (ODI) before PKP and 7 days, and 6 months after PKP, and the patient satisfaction was assessed by the modified Macnab criteria at 6 months postoperatively. Results The overall excellent and good rate of evaluation results was satisfactory. In multivariate regression, independent risk factors for poor patient satisfaction included: age ≥ 70 years (OR=2.298, 95%[CI] 1.290-4.245, P=0.025), fasting blood glucose ≥8 mmol/L (OR=2.657, 95%[CI] 1.288-4.121, P=0.016), glycosylated hemoglobin ≥6.5 mmol/L (OR=3.438, 95%[CI] 2.543-4.628, P=0.001), duration ≥8 years (OR=1.732, 95%[CI] 1.471-3.253, P=0.019) and Kyphon instrument (OR=1.472, 95%[CI] 1.112-2.228, P=0.018) were independent influencing factors of OTCF complicated with DM. Conclusion Kyphoplasty for patients with osteoporotic thoracolumbar compression fractures complicated with diabetes can achieve a satisfactory clinical effect, the curative effect is affected by many factors, attention to these factors can improve the clinical effect.